2020
DOI: 10.1007/s11367-020-01840-7
|View full text |Cite
|
Sign up to set email alerts
|

Environmental benchmarks for buildings: a critical literature review

Abstract: Purpose To reduce the environmental impact of the building sector, environmental targets considering the full life cycle of buildings can be supportive. In recent years various benchmarks based on Life Cycle Assessment (LCA) have been developed as part of regulations, labelling systems, sustainability rating tools and research studies. The objective of this paper is to critically analyse 23 existing benchmarking systems focusing on the benchmark methodology but also on the benchmark applications and communicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 15 publications
4
29
1
Order By: Relevance
“…Furthermore, the median GWP values from the Annex 72 cases appear comparable with the statistical median of benchmark systems found in Triguax et al [4], although the embodied values from the Annex 72 cases are slightly lower and full life cycle values slightly higher than said review. However, GWP values representing the full life cycle are bound to decrease following updates of operational requirements, i.e.…”
Section: Overview Of Gwp Benchmarks In Usesupporting
confidence: 82%
See 2 more Smart Citations
“…Furthermore, the median GWP values from the Annex 72 cases appear comparable with the statistical median of benchmark systems found in Triguax et al [4], although the embodied values from the Annex 72 cases are slightly lower and full life cycle values slightly higher than said review. However, GWP values representing the full life cycle are bound to decrease following updates of operational requirements, i.e.…”
Section: Overview Of Gwp Benchmarks In Usesupporting
confidence: 82%
“…Median benchmark values across limit-, reference-and target values are marked by a vertical line. Median benchmark values from the similar study of 23 benchmark systems by Trigaux et al [4] are additionally marked by dashed vertical lines in figures 1a and 1b for comparison.…”
Section: Overview Of Gwp Benchmarks In Usementioning
confidence: 99%
See 1 more Smart Citation
“…To avoid this burden shifting, it is suggested that benchmarks should consider multiple impact indicators [22]. However, such systems are currently less prevalent [23]. For example, the Netherlands are the only country with a mandatory limit value for an aggregated environmental score, which includes eleven impact indicators expressed as one environmental cost [24].…”
Section: Existing Benchmarks In Building Practicementioning
confidence: 99%
“…In order to enable a just and green transition of building construction and operation towards net-zero GHG emissions, policy makers and building design professionals, among other relevant stakeholders, require robust information on the current level of embodied carbon of buildings across Europe, as well as targets and guidance on how to reduce it going forward [8][9][10].…”
mentioning
confidence: 99%